Cancer metastasis of an unknown primary location into a postoperative kelody scar after a mine blast wound of the neck - O. O. Kovalyov; S. M. Zavhorodnii; O. P. Tolok; M. A. Kubrak; K. O. Kovalov (Patologìâ)
The connection between military trauma and cancer is not sufficiently studied. We present a clinical observation of metastasis of cancer of unknown primary localization into a keloid scar of the neck, which occurred after surgical treatment of a wound due to a previously suffered mine-explosive injury. There are no similar descriptions in the literature.